2018
DOI: 10.1620/tjem.245.167
|View full text |Cite
|
Sign up to set email alerts
|

Job Stress Factors Affect Workplace Resignation and Burnout among Japanese Rural Physicians

Abstract: Shortage of healthcare workers is a global problem. It is important to clarify factors, including job stress, that influence workplace resignation and factors that cause burnout among rural physicians. The study was designed as a cross-sectional questionnaire survey. We sent questionnaires to town or village hospitals and clinics (n = 1,898) in Hokkaido, Tohoku, Shikoku, and Kyushu and Okinawa. The number of participants was 509. Of these 7.7% were female and 21.6% were< 50 years. Internal or general medicine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
1
10
0
2
Order By: Relevance
“…However, the MBI was not measured in this study; therefore, evaluating the validity of the Japanese version of the single-item measure on the Mini-Z 2.0 was not possible. The data from this study showed a burnout rate of 34.6%, which was comparable to that in several previous burnout studies of primary care physicians, internists, and postgraduate residents in Japan ( 8 - 10 ), suggesting sufficient criterion-related validity. However, additional studies using the MBI are needed to improve the validity of the Japanese version of the Mini-Z 2.0 survey.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, the MBI was not measured in this study; therefore, evaluating the validity of the Japanese version of the single-item measure on the Mini-Z 2.0 was not possible. The data from this study showed a burnout rate of 34.6%, which was comparable to that in several previous burnout studies of primary care physicians, internists, and postgraduate residents in Japan ( 8 - 10 ), suggesting sufficient criterion-related validity. However, additional studies using the MBI are needed to improve the validity of the Japanese version of the Mini-Z 2.0 survey.…”
Section: Discussionsupporting
confidence: 86%
“…In recent years, interest in physician burnout has increased in Japan (8)(9)(10). The Japan Chapter of the American College of Physicians' (ACP) Physician Well-Being Committee (PWC) was established in June 2019 to address the issue of physician burnout in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Одним из важных факторов успешности для сельских врачей оказывается их вовлеченность в местное сообщество, которая выступает одновременно возможностью для построения успешной «сельской» карьеры и защитой от возможного профессионального выгорания. Этот фактор влияет как на удовлетворенность молодых врачей работой, так и на мотивацию к ее продолжению [Saijo, Yoshioka et al, 2018;Кобякова и др., 2017].…”
Section: трудовая повседневность мотивация и удовлетворенность молодых сельских врачейunclassified
“…Degree centrality index was calculated using Formula (1). Standardizing the values for comparing degree centrality (Formula [2]) is necessary.…”
Section: Data Measuresmentioning
confidence: 99%
“…Healthcare workers are the first resource for PHC services [1]. However, the shortage of PHC workers is a global problem, and such concern is especially serious in rural areas [2]. In China, only 1.8 physicians per 1000 people were available in rural areas in 2018, a figure equivalent to only 45% of their counterparts for urban areas [3].…”
Section: Introductionmentioning
confidence: 99%